1997
DOI: 10.1590/s0036-46651997000200007
|View full text |Cite
|
Sign up to set email alerts
|

RESISTANCE TO OXAMNIQUINE OF A Schistosoma mansoni STRAIN ISOLATED FROM PATIENT SUBMITTED TO REPEATED TREATMENTS

Abstract: A strain of Schistosoma mansoni (R1) was isolated from patient previously submitted to four treatments with oxamniquine, and to another one with praziquantel. The results obtained with chemotherapeutic test, by using oxamniquine in mice infected with the strains R1 and LE (standard), showed an evident resistance to the drug in worms of the strain R1. Thus, at the dose of 250 mg/kg oxamniquine, all mice (17) infected with the LE strain did not show surviving worms, whereas 12 out of 17 mice infected with the R1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…It is widely known that Schistosoma mansoni geographical strains exhibit variability related to infectivity, prepatent period, fecal egg excretion, liver or intestinal egg counts and altered response to schistosomicidal drugs in rodent models (Kassim et al 1979, Coelho et al 1997, Incani et al 2001, Yoshioka et al 2002, Bonesso-Sabadini & Dias 2002. However, little attention has been paid to the biological characteristics of sympatric human and murine strains.…”
mentioning
confidence: 99%
“…It is widely known that Schistosoma mansoni geographical strains exhibit variability related to infectivity, prepatent period, fecal egg excretion, liver or intestinal egg counts and altered response to schistosomicidal drugs in rodent models (Kassim et al 1979, Coelho et al 1997, Incani et al 2001, Yoshioka et al 2002, Bonesso-Sabadini & Dias 2002. However, little attention has been paid to the biological characteristics of sympatric human and murine strains.…”
mentioning
confidence: 99%
“…The effects of such factors can be serious when only one fecal sample is collected from each subject. Oxamniquine resistant worms, mentioned by Cioli et al (1978), Coura et al (1980), Prata et al (1980), Bina and Prata (1980), Dias et al (1982), Kloetzel (1982) and Coelho et al (1997) also set important limits on the evaluation of prevalence, parasite burden, and risk of infection. All such drawbacks notwithstanding, given the fact that the parasitological surveys were comprehensive, it can be concluded that the prophylactic measures introduced in Bananal succeeded in reducing schistosomiasis prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported strains of S. mansoni resistant to oxamniquine (Coelho et al 1997). On the other hand, the dose of this drug has varied from treatment to treatment.…”
Section: Discussionmentioning
confidence: 99%